Políticas de contratación de recursos humanos y la eficiencia operativa en la Municipalidad Provincial de Ucayali Contamana 2024 - Ramirez Caicedo, Ronaldo (2024)
The final report aims to determine the relationship between human resource hiring policies and operational efficiency in the Provincial Municipality of Ucayali Contamana 2024. In which a basic type study was chosen, descriptive correlational level with a non-experimental design, taking 80 workers as a sample, to whom a questionnaire was used to collect information. The results show that the human resource hiring policy is regular according to 29%. This is because the skills required for each position are clear and appropriate to their responsibilities, although sometimes the calls for applications are published late in digital media. A psychological exam is also carried out during the selection process. Finally, the hiring managers sometimes request the signature on the original documents presented by the winner before signing the contract. Regarding operational efficiency, it is considered regular by 29%, since sometimes the established production objectives are achieved and sometimes there is effective communication between the work teams. It is also observed that the promotion of personal growth and improvement within the institution is carried out intermittently. Determining that there is a significant positive relationship between staff recruitment policies and operational efficiency, with a coefficient of 0.830 and a bilateral significance of 0.000. Keywords: Hiring policies; Operational efficiency